Pengaruh Modal Sendiri, Total Aset, Volume Usaha, Jumlah Anggota dan Modal Luar terhadap Sisa Hasil Usaha Koperasi Simpan Pinjam - Pratama, Andika Canggah; Tubastuvi, Naelati; Rahmawati, Ika Yustina; Kharismasyah, Alfato Yusnar (Universitas Batanghari, 2024)
This research aims to determine the influence of own capital, total assets, business volume, members and outside capital on the remaining business results in Savings and Loans Cooperatives. Sampling in this research used a purposive sampling method by analyzing 32 cooperatives from 83 Savings and Loans Cooperatives in Banyumas Regency from 2019-2022. Data analysis was carried out using the multiple linear regression method. The results of this research show that the variables of own capital, business volume, have a positive and significant effect on the remaining business results, while the variables total assets, members, external capital do not have a significant effect on the remaining business results. The research results showethat own capital is a variable that has a relatively large influence on the remaining business results, so it is best for savings and loan cooperatives to maintain the condition of their own capital structure, and try to develop their members so that members increase the amount of principal savings and mandatory savings, so that they can increase their own capital.